1996
DOI: 10.12693/aphyspola.89.625
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Standing Waves and Rutherford backscattering Studies of the Structure of Si Single Crystals Implanted with Fe Ions

Abstract: The X-ray standing wave and Rutherford backscattering spectroscopy in channelling geometry were applied for the investigation of the structure of silicon single crystals implanted with 80 keV Fe ions. Both methods were used for the determination of crystal damage and lattice location of implanted metal atoms before and alter thermal annealing. Both methods gave consistent results regarding the amorphization of Si due to the Fe-ion implantation. Moreover, using both methods some Fe substitution fraction was det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…The minimum on curve 1 occurs because field 1 does not interact with impurities and field 2 is not excited in this angular region. If impurity atoms are randomly distributed [in (86), exp(−W a ) = B = 0], this effect is compensated entirely by increasing the interaction with field 1 (curve 2 in Fig. 28b).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The minimum on curve 1 occurs because field 1 does not interact with impurities and field 2 is not excited in this angular region. If impurity atoms are randomly distributed [in (86), exp(−W a ) = B = 0], this effect is compensated entirely by increasing the interaction with field 1 (curve 2 in Fig. 28b).…”
Section: Methodsmentioning
confidence: 99%
“…Described above approach of multilayer crystal was used in the papers [85,86] where silicon crystals were implanted with F e and N i ions and analysed with XSW technique and Rutherford backscattering (RBS) method. The XSW technique was applied previously [8,58,87] for structure investigation of Si crystals after implantation with the different impurity atoms (As, Bi).…”
Section: Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was concluded that the EXAFS results are consistent with Fe being located at a distorted interstitial site. Vartanyantz et al 29 investigated Si implanted with 5 ϫ 10 15 cm −2 of Fe at 80 keV and annealed at 750°C using Rutherford backscattering spectroscopy and channeling ͑RBS/C͒ They found that the RBS signal from Fe was reduced by 30% for ͗111͘ channeling incidence, from which they concluded that 30% of Fe would be located on substi-tutional sites. However, this conclusion is ambiguous since reductions in the backscattering yield for ͗111͘ channeling may result not only from substitutional but also from a large variety of interstitial sites in Si.…”
Section: Introductionmentioning
confidence: 99%